Branding Collective Actions: The Analysis of Visual Semiotics Used by the Active Groups Within the Walls of South Nicosia, Cyprus - Panayides, Omiros; Marina, Hadjilouca (My University, 2019)
The public realm of a city is often considered to be a ‘contested space’ on the grounds that in all contemporary cities there are disputes surrounding the issues of domestication and privatization. In most cities there are also debates about equality in class, gender, age and ethnicity (F. Graffikin et al., 2010). For the site of our research, we have chosen the walled part of South Nicosia, Cyprus, which over the last five years has been undergoing gentrification and domestication. In this paper, we will discuss the value of visual semiotics used in grassroots political actions within the public sphere. More specifically, we will analyse the logotypes and symbols used by different groups for political actions they have staged within the walled part of South Nicosia from 2008 onwards. These actions are divided into two categories: a) physical collective actions (demonstrations, protests, etc.), b) linguistic landscapes (Landry & Bourhis, 1997; Shohamy, Ben-Rafael & Barni, 2010) found in the walled city (traces of physical collective action, action without physical presence, etc.). By presenting specific actions staged by different groups active within South Nicosia, we hope to make a case for how these groups brand themselves and their political actions and how their branding changes depending on the context of the action. Finally, we will discuss how these symbols tell the narrative of the city’s political atmosphere and its development.
Keywords: Branding; Collective actions; Linguistic landscapes